Molecular Weight and Structural Properties of Biodegradable PLA Synthesized with Different Catalysts by Direct Melt Polycondensation - Hyung Woo Lee; Rizki Insyani; Daniel Prasetyo; Hermawan Prajitno; Johnner P. Sitompul (Institute for Research and Community Services, Institut Teknologi Bandung, 2015)
Production of biodegradable polylactic acid (PLA) from biomassbased lactic acid is widely studied for substituting petro-based plastics or polymers. This study investigated PLA production from commercial lactic acid in a batch reactor by applying a direct melt polycondensation method with two kinds of catalyst, Î³-aluminium(III) oxide (Î³-Al2O3) or zinc oxide (ZnO), in reduced pressure. The molecular weight of the synthesized PLA was determined by capillary viscometry and its structural properties were analyzed by functional group analysis using FT-IR. The yields of polymer production with respect to the theoretical conversion were 47% for Î³-Al2O3 and 35% for ZnO. However, the PLA from ZnO had a higher molecular weight (150,600 g/mol) than that from Î³-Al2O3 (81,400 g/mol). The IR spectra of the synthesized PLA from both catalysts using polycondensation show the same behavior of absorption peaks at wave numbers from 4,500 cm-1 to 500 cm-1, whereas the PLA produced by two other polymerization methods